Effect of innovation in communication message on financial customer relationships: New evidence from Saudi Arabia - Al-Nsour, Abdulrahman Ibrahim Al-Ayyaf Iyad Abdel Fattah (Journal of Asian Business Strategy, 2024)
The study aimed to measure the impact of innovation in the communication message on the financial customer relations of the companies listed in stock market in Saudi Arabia "TADAWL", as well as to determine the level of significant difference in perception level of innovation and customer relations according to demographics. The study consists of two populations. The first is all companies listed in the Saudi stock market "TADAWL" that apply marketing innovation. The total companies reached 38 in six key sectors in the economy: consumer services, food retailing, food production, health care, banks, and communications. The second population is all the customers of the listed companies. The research methodology used a full survey method to collect data from companies, and the convenience sample technique was used. Total of Customers reached 500. The study concludes innovation in the communication message- content and design – have a high degree of perception. The study also concludes a strong positive impact of innovation in the content on financial relationships of the listed companies in TADAWL. The statistical differences show significant differences in the innovation in message design according to financial resources of innovation tended to 10% or more, and no such differences in the customer financial relationships according to all demographics. Finally, the presented a set of recommendations that enhance the innovation and financial relationships in the surveyed companies in Saudi Arabia.